Electrophilic Alkylations of Vinylsilanes: A Comparison of α‐ and β‐Silyl Effects. Issue 4 (16th December 2013) - Laub, Hans A.; Mayr, Herbert
Abstract Kinetics of the reactions of benzhydrylium ions (Aryl2CH+) with the vinylsilanes H2CC(CH3)(SiR3), H2CC(Ph)(SiR3), and (E)‐PhCHCHSiMe3 have been measured photometrically in dichloromethane solution at 20 °C. All reactions follow second‐order kinetics, and the second‐order rate constants correlate linearly with the electrophilicity parameters E of the benzhydrylium ions, thus allowing us to include vinylsilanes in the benzhydrylium‐based nucleophilicity scale. The vinylsilane H2CC(CH3)(SiMe3), which is attacked by electrophiles at the CH2 group, reacts one order of magnitude faster than propene, indicating that α‐silyl‐stabilization of the intermediate carbenium ion is significantly weaker than α‐methyl stabilization because H2CC(CH3)2 is 103 times more reactive than propene. trans‐β‐(Trimethylsilyl)styrene, which is attacked by electrophiles at the silylated position, is even somewhat less reactive than styrene, showing that the hyperconjugative stabilization of the developing carbocation by the β‐silyl effect is not yet effective in the transition state. As a result, replacement of vinylic hydrogen atoms by SiMe3 groups affect the nucleophilic reactivities of the corresponding CC bonds only slightly, and vinylsilanes are significantly less nucleophilic than structurally related allylsilanes.